Understanding Predictability - Menzly, Lior; Santos, Tano; Veronesi, Pietro (Journal of Political Economy, 2004)
We propose a general equilibrium model with multiple securities in which investors' risk preferences and expectations of dividend growth are time-varying. While time-varying risk preferences induce the standard positive relation between the dividend yield and expected returns, time-varying expected dividend growth induces a negative relation between them. These offsetting effects reduce the ability of the dividend yield to forecast returns and eliminate its ability to forecast dividend growth, as observed in the data. The model links the predictability of returns to that of dividend growth, suggesting specific changes to standard linear predictive regressions for both. The model's predictions are confirmed empirically.